Konstitucionalizacija uporabe gotovine in ustavnorevizijska nomotehnika - Bardutzky, Samo (Pravni letopis, 2025)
One of the several proposals for the revision of the Constitution of the Republic of Slovenia raised before the 9th National Assembly concerned the introduction of a new constitutional right to use cash. The primary focus of this article is not to discuss the merit of this proposal but rather an analysis of two proposed (alternative) texts of the potential new constitutional provisions. The first proposal was formulated by a group of voters and the second one by the expert group of the Constitutional Committee. The article analyses the two texts on the basis of rules applicable to interpretation and use of human rights and fundamental freedoms. The article purports to assess objectively the potential ways of interpreting the proposed provisions regarding the holders of the potential new right, its content as well as potential limitations and legislative implementation. For the purpose of the discussion on the drafting of the constitutional text and to enable a comparison of parallel possible texts the article concludes by formulating a third option and presenting its advantages.
Keywords: constitutional reform; constitutional revision; constitutionalisation; človekove pravice in temeljne svoboščine; določitev načina uresničevanja človekove pravice; gotovina; human rights and fundamental freedoms; konstitucionalizacija; legislative drafting; legislative implementation of human rights and fundamental freedoms; limitations on human rights and fundamental freedoms; nomotehnika; poseg v človekove pravice; sprememba ustave; use of cash; ustavna revizija